Identität und Sprache des Migranten in der Fremde im Werk von Franco Biondi - Brunner, Maria E. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Seen from the point of view of literary-sociological studies, Franco Biondi’s works are part of the migrant and foreign literatures which emerged in Germany in the wake of the recruitment of foreign labour starting in the 1950s. This literature – written by authors who are not Germans in the sense of the old German nationality and citizenship legislation, but who live in Germany and have their works published in the German language area – was formerly called ‘guest-worker literature’. Then, in the 1980s, it was referred to as a literature of ‘shock and stunned silence’, and in the 1990s as ‘migrant literature’ or ‘literature of foreign parts’. The theme in Biondi ’s works is the break with origin and the process of ‘coming-to-language’ of the identity that is forming through the medium of language in the encounter with the foreign. Immigration for Biondi becomes immigration into a new language.